The development of the Bulgarian literary language from incunabula to first grammars, late fifteenth-early seventeenth century - Petrov, Ivan (Philologist) (Studies in Slavic, Baltic, and Eastern European languages and cultures, 2021)
"This book is devoted to the history of the first printed Cyrillic books and their role in the development of the Bulgarian literary language. Ivan N. Petrov presents this history in a broad context of linguistic, terminological, and source-related issues of South Slavic writings and Cyrillic printing of the Eastern Slavs"--